Physical activity and sedentary behaviour in secondary prevention of coronary artery disease: A review - Vasankari Ville; Halonen Jari; Vasankari Tommi; Anttila Vesa; Airaksinen Juhani; Sievänen Harri; Hartikainen Juha (Elsevier, 2025)
Comprehensive management of coronary artery disease (CAD) includes physical exercise as a part of daily lifestyle therapy. Still CAD patients generally have low physical activity (PA) and high sedentary behaviour (SB). This review summarizes the effect of exercise training and habitual PA and SB on physical fitness and quality of life (QoL) as well as on rehospitalizations and mortality in patients with stable CAD, recent acute coronary syndrome (ACS) or recent revascularization. A literature review of the influence of exercise, and PA and SB profiles in secondary prevention of CAD was performed using PubMed. All articles published between January 2001 and April 2019, meeting the inclusion criteria were considered. A total of 25 cross-sectional or prospective studies or randomized controlled trials (RCT) were included to this review. Exercise training was found to improve maximal oxygen consumption, QoL, and to reduce rehospitalizations and mortality among patients with established CAD. Remote PA interventions have not been as effective as the supervised exercise sessions in reducing the clinical endpoints. High SB, especially when combined to low PA, is associated with poor cardiorespiratory fitness and worse long-term prognosis among patients with ACS. In conclusion, exercise training and high PA are beneficial for patients with stable CAD, recent ACS or recent revascularization. High SB is associated with poor cardiopulmonary fitness and increased mortality in ACS patients. Novel tools using online applications and smart devices are promising means to offer remote guidance for PA among patients unable to participate in regular exercise sessions.